Residual film thickness following immiscible fluid displacement in noncircular microchannels at large capillary number. Issue 9 (17th April 2018) - Lu, Yu; Kovalchuk, Nina M.; Simmons, Mark J. H.
Abstract : An experimental study of the displacement of one immiscible fluid by another was performed in microchannels with circular, square and near‐semicircular cross‐sections, with hydraulic diameters from 100 to 200 μm. Experiments were performed over a range of capillary number, Ca, from 0.02 < Ca < 80, with viscosity ratios between the two fluids ranging from 20 to 100. The liquid film left on the channel wall following the advance of the displacing fluid was obtained from visual measurements and a method for the estimation of mean film thickness was shown to be in good agreement with existing correlations. The addition of a surfactant (Sodium Dodecyl Sulfate, SDS) dissolved in the displacing fluid led to a reduction in the thickness of the residual film. © 2018 The Authors AIChE Journal published by Wiley Periodicals, Inc. on behalf of American Institute of Chemical Engineers AIChE J, 64: 3456–3466, 2018